PERANAN IMAM SYAHID HASAN AL-BANNA DALAM MENGEMBANGKAN IKHWANUL MUSLIMIN DI MESIR PADA TAHUN 1928-1949 - Sakinatul Hayati Sakinatul Hayati; Isjoni '; Marwoto Saiman Marwoto Saiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: The background of this thesis is the founder Hasan al-Banna an organization's largest Muslim movement that was first established in Egypt, namely the Muslim Brotherhood. The Muslim Brotherhood was founded as a form of community dissatisfaction with the Egyptian government at that time. The purpose of this study was to determine the short history of the collapse of the Ottoman Empire, to find out the history of the life of Hasan al-Banna, to know the history of the Muslim Brotherhood, to find out the struggle Hasan Al-Banna alongside the Muslim Brotherhood, to determine the role of the Muslim Brotherhood against independence Indonesia, to seek out the end of the struggle of Hasan al-Banna, to figure out which forms part of Hasan al-Banna carried out in developing the Muslim Brotherhood. Penelit method is the method of Historical and Descriptive. The aim is to reconstruct, analyze, evaluate, and explanation of evidence to get the facts reach conclusions that can be justified. The results showed that the Muslim Brotherhood is an organization Jihad, Propagation, and Politics by pemehaman Syumuliah al Islam (Islamic Universalism) kehidupan.mengenai covering all aspects of this case, as evidence of Martyrs Imam Hasan Al - Banna has established a charitable foundation, education, politics and Jihad for establishing the Muslim Brotherhood. In the field of education for example has many established foundations of Islamic-based educators to print cadres Propagation successor Jihad movement in the world . And in the political sphere of the Muslim Brotherhood was greatly feared by opposing political elite at the time, the Muslim Brotherhood have participated in the elections that took place in Egypt and could win. This victory did not reduce their main intention, namely jihad in Allah's way, but rather be part of the vision of the organization that brings the goodness of all life. The entry of the Muslim Brotherhood Political kemedan is a natural process that aims to fix a number of irregularities that occurred in Egypt .Keywords : Hasan al - Banna , the Muslim Brotherhood